Researches of biological activity of lectin-containing extracts of pale coneflower (Echinacea pallida (nutt.) Nutt.) - Поспєлов, С. В.; Шершова, С. В. (Scientific Progress & Innovations, 2012)
The experimental data assessment biological activity of the lectin containing extracts of pale coneflower (Echinacea pallida (nutt.) Nutt.) cv. “Beauty of praries” and their components by testing on watercress salad sprouts are given. It has been established that the concentration of 10–1% depressing roots the test system. The stems extract and theirs components had been the most evident stimulating effect (+25.3%), and lectins fraction of extract of rhizomes with roots(+15.3%). In the majority of variation the complete extract of inflorescences slightly stimulated growth of watercress salad, but their components shown as stimulate activity(+25.3% )as depressing activity(- 23.5%).The extracts of leaves had allopathic effect the almost in whole range concentration. The following conclusion a drown that hormonal effect the extracts of pale coneflower is possible.